HUBUNGAN SCREEN TIME DENGAN KEJADIAN MIGRAIN PADA MAHASISWA KEDOKTERAN UNIVERSITAS JAMBI ANGKATAN 2018 - Mauli Datul Hasanah; Ima Maria; Mirna Marhami Iskandar; Attiya Istarini; Patrick William Gading (Journal of Medical Studies, 2022)
ABSTRACT Background: Migraine is one of the most common primary headache complaints. Migraine can occur due to trigger factors including foods with certain ingredients (such as tyramine, chocolate), menstrual cycles, weather, sleep patterns, bright light, and screen time. Screen time is the total time spent viewing or watching gadget screens such as televisions, computers (laptops), smartphones, tablets and video games. Objectives: To determine the relationship between screen time and the incidence of migraine in medical students at Jambi University. Methods: This research is a quantitative analytic study with a cross sectional design. Respondents consisted of 93 medical students at Jambi University Batch 2018 who were taken by the total sampling method and had met the inclusion and exclusion criteria. Screen time data and migraine incidence were assessed using a questionnaire. Analysis of the relationship between the two variables was tested by chi-square test and processed with SPSS version 25. Results: The results showed that there was a significant relationship between screen time and the incidence of migraine. Conclusions: the longer the use of screen time, the higher the incidence of migraine in medical students at Jambi University batch 2018. Keywords: Migraine, Screen time ABSTRAK Latar belakang: Migrain merupakan salah satu keluhan nyeri kepala primer yang paling sering ditemukan. Kejadian migrain dapat terjadi karena adanya faktor pemicu diantaranya makanan dengan kandungan tertentu (seperti tiramin, cokelat), siklus menstruasi, cuaca, pola tidur, cahaya yang terang, dan screen time. Screen time adalah waktu total yang dihabiskan untuk melihat atau menonton layar gadget seperti televisi, komputer (laptop), smartphone, tablet dan video game. Tujuan: Mengetahui hubungan antara screen time dengan kejadian migrain pada mahasiswa kedokteran Universitas Jambi. Metode: Penelitian ini merupakan penelitian analitik kuantitatif dengan desain cross sectional. Responden terdiri dari 93 mahasiswa kedokteran Universitas Jambi Angkatan 2018 yang diambil dengan metode total sampling dan telah memenuhi kriteria inklusi dan eksklusi. Data screen time dan kejadian migrain dinilai dengan kuisioner. Analisis hubungan antara dua variabel diuji dengan uji chi-square dan diolah dengan SPSS versi 25. Hasil: Hasil penelitian didapatkan adanya hubungan antara screen time dengan kejadian migrain. Kesimpulan: Semakin lama penggunaan screen time maka akan meningkatkan kejadian migrain pada mahasiswa kedokteran Universitas Jambi angkatan 2018. Kata kunci: Migrain, Screen time